Penerapan Sistem Pengendalian Internal Pemerintah sesuai PP 60 Tahun 2008 dan Sistem Informasi Akuntansi Berbasis Artificial Intelligence Terhadap Kecenderungan Fraudulent Financial Reporting : (Studi Kasus pada Organisasi Sektor Publik di Kabupaten Gresik) - Prayogi, Gusti Dian (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Abstrak— For public sector organizations Artificial Intelligence can improve efficiency, transparency, and the quality of services provided to the public if its application is appropriate, as for some technologies in the public sector, for example E-Government, Big Data Analytics and Open Data. This type of research analysis uses quantitative research methods. The research analysis population used was from the Finance and Accounting Section of the Gresik Work Unit, East Java Regency. The sampling technique is target sampling (Proposive). Researchers used a questionnaire to collect data. The developed questionnaire was tested quantitatively with validity and reliability tests. The indicators of the research analysis tool used as variables are the government internal control system (X1), artificial intelligence-based accounting information systems (X2), and financial reporting fraud trends (Y). In this study, descriptive analysis using load factor values and inferential analysis using smartPLS 3.0 software were used as data analysis. The results of the study state that the government internal control system does not have a significant impact on the tendency of fraud in financial statements with a positive coefficient of 0.103. However, the Artificial Intelligence-based accounting information system has a significant effect on the tendency of financial statement fraud with a coefficient value of 0.637.